Impact of mobility restrictions on active aging; cross-sectional associations and longitudinal changes parallel to COVID-19 restrictions. (January 2022) - Portegijs, Erja; Saajanaho, Milla; Leppä, Heidi; Koivunen, Kaisa; Eronen, Johanna; Rantanen, Taina
Highlights: Individuals' active aging refers to an overall active approach to life. Active aging covers one's will, ability, opportunity and extent of doing activities. Individuals with limited neighborhood mobility obtain lower active aging scores. Active aging scores declined similarly regardless of baseline neighborhood mobility. Engagement in several activities is possible despite limited neighborhood mobility. Abstract: Background: Meaningful activities can be done in or around home, but opportunities for participation and active aging decrease when moving in smaller areas. Active aging refers to having an active approach to life in line with one's goals, ability and opportunities. In adults over 75 years with different baseline neighborhood mobility levels, we studied active aging scores two years prior to and amid COVID-19, when governments restricted mobility of residents to slow the COVID-19 outbreak. Methods: AGNES cohort data were collected in 2017–2018 and spring 2020. Individuals were queried about their will, ability, and opportunity, and extent of doing 17 activities, and subsequently, item, composite and sub-scores of active aging were computed. Neighborhood mobility was assessed as frequency of moving in or beyond own neighborhood (limited, regular, daily=reference). Associations were studied using Generalized Linear Models (cross-sectionally, n  = 1007) and General Estimating Equations (prospectively, n  = 774). Results: Participants with limited baseline neighborhood mobility had lower active aging scores than those with daily mobility, but the decline over time was similar. Some item scores on opportunity to act and extent of doing, e.g. for making one's day more interesting and advancing matters of faith or worldview, were better retained amid COVID-19 by those with limited mobility, attenuating group differences. Conclusions: Active aging scores were somewhat compromised in individuals with limited neighborhood mobility, but opportunities for and engagement in several activities seemed to be better retained amid COVID-19 than for those with daily mobility. Thus, active aging may be possible despite mobility restriction.